Evidence on the determinants of productivity in Brazil, 2004-2014 - Souza, Thais Andreia Araujo de (2020)
In Brazil, productivity has been underperforming since the 1980s. Thus, considering its importance for economic growth, it is important to verify ways to stimulate its performance. Therefore, this study aims to verify how some determinants influenced the productivity, being used the methodology of structural autoregressive vectors. It was verified that effects of the improvements in the determinants would only occur in a longer time horizon, also that the infrastructure had a greater effect on productivity, both in the short and the long run. Therefore, improvements in terms of infrastructure have a greater effect on productivity, and consequently on economic growth.